Changes in edible oil preference and present-day consumption status of households : A case of Tamil Nadu state, India: EDIBLE OIL PREFERENCE AND PRESENT CONSUMPTION OF HOUSEHOLDS: A CASE OF TAMIL NADU - G N GOVINDARAJ; S SURYAPRAKASH; N SIVARAMANE; P MURALI (Journal of Oilseeds Research, 2016)
Traditionally, in India, a variety of edible oils are used for consumption. The type of edible oil being consumed varied across regions. While one region prefers rapeseed-mustard oil, the other region enjoys peanut, sesame and coconut oils. On the whole, rapeseed and mustard oil and peanut oil are the most popularly consumed edible oils in the country. In the study state, Tamil Nadu, the foremost edible oil consumed is peanut oil besides other oils. The technological, economic and policy changes after liberalization induced drastic changes in consumer’s preference for food including edible oils. The Markov Chain Analysis for rural and urban Tamil Nadu revealed that there is a perceptible shift in edible oil consumption from traditional peanut oil to Other Edible Oils (OEO’s). The possible reason for these shifts are increased urbanization and changing lifestyles, increased awareness, availability of oils in loose pack form in varied quantities available even in remote areas, change in relative prices of oils, and increased income levels ofrural and urban households. The secondary data published byNational Sample SurveyOrganisation for Tamil Nadu state did not clearly disintegrate the OEO’s, primary survey was employed for this study. The results based on 1000 households revealed that the dominant edible oil consumed was non-traditional sunflower oil in both rural and urban regions. The per capita consumption of edible oils was also higher in recent years indicating higher consumption demand. The results from this study affirm that peanut oil, which was traditionally consumed by households as first preference, has been replaced by non-traditional oils like sunflower oil owing to various macroeconomic factors like price, cost of cultivation and imports. The change call for more concerted efforts to supply these non-traditional oils in the future as the demand were expected to be high. Further, it also implies need for increasing the capacities of edible oil industries as the overall consumption of edible oil is increasing over years. This study highlights the need for suitable policy options for edible oil processing and marketing specifically for sunflower oil besides traditional oils and trade on edible oils.